2017
DOI: 10.1016/j.rbmo.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, controlled trial comparing two doses of oestrogen therapy after hysteroscopic adhesiolysis to prevent intrauterine adhesion recurrence

Abstract: The aim of this prospective, randomized, controlled trial was to evaluate the efficacy of different doses of oestrogen treatment (2 mg and 6 mg daily) after hysteroscopic adhesiolysis in patients with moderate to severe adhesion according to the American Fertility Society (AFS) classification of intrauterine adhesions. A total of 121 patients were included in the final analysis. Fifty-nine patients received 2 mg oestrogen daily (low-dose group), and 62 received 6 mg oestrogen daily (high-dose group) for three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 25 publications
1
37
0
1
Order By: Relevance
“…No superior effect of the high dosage was demonstrated 69. When comparing 2 mg and 6 mg in a prospective, randomized trial, no benefit was demonstrated in the 6 mg arm 70…”
Section: Management Of Asmentioning
confidence: 97%
“…No superior effect of the high dosage was demonstrated 69. When comparing 2 mg and 6 mg in a prospective, randomized trial, no benefit was demonstrated in the 6 mg arm 70…”
Section: Management Of Asmentioning
confidence: 97%
“…No significant difference was reported between different doses ranging from 2 mg to 12 mg (Xiao et al, 2014;Guo et al, 2017;Guo et al, 2019;Liu L et al, 2019), but in the study by Liu AZ et al (2016), the use of a larger amount of oestradiol (9 mg daily) is significantly better than the group taking 3 mg daily. Chen et al (2010) reported that a larger amount of oestrogen may induce fibrosis of the endometrium.…”
Section: Strengths and Limitationsmentioning
confidence: 88%
“…However, it is difficult to completely seal the wound surfaces due to the possible risks of endometrial ischemic necrosis, abnormal bleeding, infection, contraceptive ring incarceration, and uterine perforation. The use of estrogen is the main method to promote endometrial regeneration and repair, but the efficacy of this method depends on whether there is enough residual endometrial tissues and on the dosage of estrogen used (17,18). Many scholars have committed to seek effective methods for preventing and treating recurrence of IUA postoperatively.…”
Section: Perplexity For the Treatment Of Iuasmentioning
confidence: 99%